Presence of Organic Micropollutants in Agricultural Waters and Soils (TERRA LATINOAMERICANA, 2024)
Using gas chromatography coupled with mass spectrometry, the concentrations of organic micropollutants (OMP) in irrigation water were determined in 15 plots located in the Atlixco-Izúcar Valley in Puebla, Mexico. Similarly, pollutant concentrations were determined in soils irrigated with water from the Sinú River in the river basin (same name) in the Department of Córdoba, Colombia. Both in Mexican irrigation waters Colombian soils, the OMP concentration analyzed far exceed the values found in similar matrices in agricultural environments in Spain. These results indicate the need to attend to monitoring and adequately treating water for irrigation.
Keywords: anthropic compounds; cropland; Mexico; Colombia